Pengembangan dan Pembangunan Berkelanjutan pada “Sekaran Edukasi Maggot” Berbasis Green Economy dan Ecotourism - Marsha Savira Agatha Putri; Fadlilah, Anik; Rusminah, Sani; Pratama, Feby Hidayah; Wahyuni, Wahyuni (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sekaran Lamongan Village has a progressive business unit in developing the economic sector in the tourism sector, especially educational tourism, which was initiated by BUMDes Sekaran in 2021, namely Educational Tourism “Sekaran Edukasi Maggot (Semaggot)”, which is an educational tourism site for the integration of waste management cultivation with Maggot-Chicken-Lele cultivation. To manage and develop this educational tourism, the Lamongan Regency Tourism Office officially stipulates the Decree on the Establishment of the “Semaggot Tourism Awareness Group (Pokdarwis)”. However, the problems faced at this time are: the need to increase the production capacity of catfish farming, KUB chickens, BSF maggots requires more feed stock. So, it is necessary to add alternative feed from silk worms and requires efforts to market cultivation products based on digital marketing transformation. So, there is a need for training in silk worm cultivation which also utilizes organic waste processing into eco-enzyme as a medium for silk worm growth (green economy). In addition, there is a need for training on the creation and use of e-commerce accounts for members of Pokdarwis Semaggot so that they can expand the marketing network for cultivated products. From this training activity, the participants' level of understanding of the green economy training material increased by an average of 28% and 39% on the material of marketing digitization and the use of e-commerce. In addition, partners can also reduce the capacity of organic waste by 11% which is used as an eco-enzyme. With the addition of silk worm cultivation and the addition of catfish seedlings, the cultivation production capacity has increased by 34%. The net profit of product sales increased from 2022, 2023, 2024 respectively, including 6,784,300, 6,928,000, 7,567,800. Future plans include market research analysis, branding training, content development on social media and other digital platforms, as well as educational activities and events.